A Synergistic Antibacterial Platform Combining Low-Temperature Photothermal Therapy and Antibiotic Therapy - Qiming Zhang; Lei Chang; Caixia Sun; Wanchao Zuo; Shibo Zhang; Cong Liu; Shuyue Deng; Pengcheng Wu; Panpan Dai; Jianjun Dai; Yanmin Ju (MDPI AG, 2023)
Antimicrobial resistance has brought great burden to global public health. Alternative strategies are needed to reduce the development of drug resistance. Herein, we have developed an effective synergistic antibacterial strategy combining low-temperature photothermal therapy (LT-PTT) with antibiotic therapy, improving the bactericidal efficiency to avoid antimicrobial resistance. Copper sulfide templated with bovine serum albumin (CuS-BSA) nanoparticles were selected as the photothermal agent, and co-loaded into the hydrogel (Gel) with mupirocin. The Gel could slow down the release rate of CuS-BSA and mupirocin, thereby prolonging the effective drug reaction time. More importantly, when applying near-infrared laser irradiation, the antibacterial activity of the platform could be enhanced greatly by LT-PTT effect of CuS-BSA nanoparticles. In vitro and in vivo results both confirmed that the antibacterial efficacy of the synergistic therapeutic strategy was improved greatly with complete bacterial removal. Overall, this platform has posed a potential strategy to reduce the development of drug resistance and improve patient compliance.